What counts as sustainability?: a sociospatial analysis. Issue 4 (2nd October 2021) - Beasy, Kim; Corbett, Michael
ABSTRACT: Sustainability is a ubiquitous term today and one that is central to key environmental and social policy discussions relating to the most pressing questions faced in contemporary societies. In this paper we argue that sustainability needs to be understood in relation to social space. We do so by engaging with Pierre Bourdieu's thinking tools as well as Edward Soja's spatial analysis to deconstruct how differently positioned actors understand and relate to space, including how to sustain it. Drawing on focus group and interview data from a small Australian city, we use Soja's typology to critique spatial tropes and dualistic frames common in sustainability discourses such as ecological/social, global/local, and reveal nuanced interpretations of spatial relations.